Needs and Modification Analysis for X Hospital Dental Clinic Infrastructure in Response to Covid-19 - Kurniawan, Gladys; Hakim, Lukman; Al Rasyid, Harun; Djauhari, Thontowi (Fakultas Kedokteran Universitas Brawijaya)
This research was conducted to find the root of the problem and the solution to the inactivity of X Hospital Dental Clinic since the Covid-19 pandemic. The findings from the study are expected to be an input for the hospital to be able to immediately reopen Dental Clinic services. The research design used descriptive analysis of observation data, interviews, and literature study. The Fishbone Diagram combined with 5 WHYs is used to find the root of the problem. Determination of problem solutions using the CARL method (Capability, Accessibility, Readiness, and Leverage) through the Forum Group Discussion (FGD). The results showed that the root cause of the inactivity of X Hospital Dental Clinic since the Covid-19 pandemic was the unavailability of infrastructure in accordance with the minimum standards. Therefore, X Hospital needs to procure appropriate infrastructure and support the X Hospital Dental Clinic facilities in providing services during the Covid-19 pandemic. This procurement must be adjusted to the conditions of the space and environment around the Dental Clinic and the capabilities of the hospital. The proposed adjustment is a modification to the infrastructure that will be provided and the existing Dental Clinic facilities. The infrastructure that must be provided is related to air circulation, practice room management, and patient procedures.